Sedekah Bumi (Nyadran) as an Expression of Gratitude in Javanese and Islamic Traditions of the Sumur Village Community, Brangsong District, Kendal - Ma’sum Jauhari; Puji Widiyanti; Moh. Albib Fillah Pradana; Fariz Muhammad Rafil; Muhammad Ricki Farchani; Renjana Mantri Laras; Cendykia Syahputra Lubis; Destananda Farhan Helmi (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
Culture is the result of human thought so that it is manifested by humans in everyday life. The form of culture cannot be separated from the existence of space and time which are produced from cultural elements. Javanese society in general who live in rural areas in living and carrying out daily life is covered by various traditions.Nyadran comes from Hindu and Buddhist traditions that originated in the 15th century, and Walisongo combined this tradition with his preaching so that he could easily embrace Islam. Initially, the saints tried to straighten out the Javanese people's beliefs about animism, which in Islam is known as polytheism. To avoid misunderstandings with these traditions, the saints complemented them by taking them, filling them with verses such as the Qur'an, tahlil, and prayers. Earth Alms (Nyadran) as a form of gratitude for the Javanese and Islamic traditions of the Sumur Village Community, Brangsong District, Kendal, usually in the Sumur village they carry out the nyandran tradition right on Friday Kliwon in the month of Mubarrom (Suro). This tradition is carried out by the Sumur village community to commemorate the ancestral heritage site of the Sumur village in the form of a spring to meet the needs of the Sumur village community in the form of water before the existence of PAMDES. The event is filled with prayers addressed to the ancestors who preceded them.